BS ISO 9735-10. Electronic data interchange for administration, commerce and transport (EDIFACT). Application level syntax rules (Syntax version number: 4, Syntax release number: 2). Part 10. Syntax service directories (19th August 2021) - British Standards Institution,
No abstract available